2003
DOI: 10.1016/s0886-3350(03)00137-8
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone and flurbiprofen drops to maintain mydriasis during phacoemulsification cataract surgery

Abstract: In the presence of epinephrine in the intraocular irrigating solution, both prednisolone 1% and flurbiprofen 0.03% failed to maintain mydriasis at the crucial steps of nuclear emulsification and cortical I/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Shaikh and colleagues analyzed the antimiosis effect of topical prednisolone compared with flurbiprofen. There were no statistically significant differences between the two drugs; however, flurbiprofen produced greater mydriasis 20. It has been reported also that the preoperative use of ketorolac for 3 days is more effective in maintaining mydriasis than the regimen of 1 day and 1 hour preoperatively 13.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Shaikh and colleagues analyzed the antimiosis effect of topical prednisolone compared with flurbiprofen. There were no statistically significant differences between the two drugs; however, flurbiprofen produced greater mydriasis 20. It has been reported also that the preoperative use of ketorolac for 3 days is more effective in maintaining mydriasis than the regimen of 1 day and 1 hour preoperatively 13.…”
Section: Discussionmentioning
confidence: 79%
“…It has also demonstrated superior penetration of the intraocular tissues with adequate concentrations in the posterior segment to inhibit the synthesis of PGs 27,28,30,31. Multiple studies have demonstrated that NSAIDs are effective drugs for maintaining trans-operative mydriasis13,1620 and in preventing and treating pseudophakic CME 21–26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical NSAIDs (Non- Steroidal Anti-inflammatory Drugs) are used as preoperative medication routinely to prevent this pupillary constriction. [3233343536] In this study we have not used any preoperative NSAID, and yet the pupillary dilatation was maintained. This is an important requirement for safe removal of lens matter and is well catered by our technique of mydriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike nonsteroidal agents, steroid eye drops have not been extensively studied for their antimiotic effect. [7][8][9] Cataract surgery complications increase when miosis occurs. It was reported that, when mydriasis is greater than 6 mm, the incidence of posterior capsule rupture is reduced by half.…”
Section: Introductionmentioning
confidence: 99%